(untitled) (Research, Society and Development, 2024)
This research aimed to outline the socio-educational characteristics of children receiving physiotherapy care in a public clinic on demand. An epidemiological, descriptive and cross-sectional research was carried out in the municipality of Parnaíba, Piauí. The sample comprised 32 families, who responded to a questionnaire consisting of 10 questions, 9 of which were closed and 1 was open. This framework was designed to capture both objective responses and subjective perceptions, allowing for a comprehensive understanding of the financial, home, and school aspects of participating families. The results highlight that most families faced financial challenges, despite some receiving government benefits for children with special needs. Many families also had difficulty following medical recommendations or participating in therapeutic activities due to financial barriers. In the home context, children’s mobility emerged as a significant challenge. The analysis revealed that the majority of families do not have access to specialized equipment to improve mobility. This creates an environment where the mobility of children with special needs can be restricted, affecting their independence and quality of life. Finally, the inclusion of children with special needs in school activities is still a significant challenge. The findings provide relevant information for the development of public policies with a view to establishing formal support for our target audience.